2017
DOI: 10.2169/internalmedicine.8861-17
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial Lung Disease as an Initial Manifestation of Giant Cell Arteritis

Abstract: Interstitial lung disease (ILD) has rarely been reported as a manifestation of giant cell arteritis (GCA). We herein report a unique case of GCA in a 76-year-old woman who presented with ILD as an initial manifestation of GCA. Ten years before admission, she had been diagnosed with granulomatous ILD of unknown etiology. Corticosteroid therapy induced remission. One year after the cessation of corticosteroid therapy, she was admitted with a persistent fever. After admission, she developed left oculomotor paraly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…PPFE has never been associated with giant cell arteritis and, as far as we know, only two GCA patients with interstitial lung diseases have been described in the literature. Karam et al, in 1982 reported a case of a patient with GCA without specific interstitial lung involvement and no PPFE evidence [23] while more recently Konoshi et al described a clinical case without PPFE evidence at HRCT [24]. The lung involvement in GCA is rare and interstitial lung diseases (ILD) are usually reported as an uncommon clinical manifestation of GCA [25].…”
Section: Discussionmentioning
confidence: 99%
“…PPFE has never been associated with giant cell arteritis and, as far as we know, only two GCA patients with interstitial lung diseases have been described in the literature. Karam et al, in 1982 reported a case of a patient with GCA without specific interstitial lung involvement and no PPFE evidence [23] while more recently Konoshi et al described a clinical case without PPFE evidence at HRCT [24]. The lung involvement in GCA is rare and interstitial lung diseases (ILD) are usually reported as an uncommon clinical manifestation of GCA [25].…”
Section: Discussionmentioning
confidence: 99%
“…Aortitis is a widely recognized presentation of GCA and coronary artery involvement may lead to myocardial infarction [31]. Rare complications include pericardial effusion [32], tongue necrosis [33] and interstitial lung disease [34]. See Fig.…”
Section: Manifestationsmentioning
confidence: 99%
“…TA [7][8][9]15,16,19,[25][26][27] GCA [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] Behcet's [71][72][73][74][75][76][77][78] PAN [96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112] NSG [118][11...…”
Section: Takayasu Arteritisunclassified
“…Upper respiratory tract involvement occurs in 10% of patients and manifests as a sore throat or persistent cough [54,55]. Lower respiratory tract involvement is decidedly uncommon, but pulmonary nodules, interstitial infiltrates, lymphocytic alveolitis, subclinical alveolar hemorrhage, and pleural effusion have been reported [56][57][58][59][60][61][62]. The rare interstitial manifestations, including nodules and infiltrates, are thought to be related to granulomatous inflammation [62].…”
Section: Giant Cell Arteritismentioning
confidence: 99%
See 1 more Smart Citation